2020
DOI: 10.14202/vetworld.2020.345-353
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-I-converting enzyme inhibitory peptides in milk fermented by indigenous lactic acid bacteria

Abstract: Background and Aim: Fermented milk can be used to produce antihypertensive peptides. Lactic acid bacteria (LAB) with its proteolytic system hydrolyze milk protein during fermentation to produce several peptides, which include antihypertensive bioactive peptides. This study aimed to investigate the ability of indigenous LAB for the production of angiotensin-I-converting enzyme inhibitory (ACE-I) peptides in fermented milk and to characterize the ACEI peptides. Materials and Methods: Reconstituted milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Viable counts of the LAB ranged from 9.18 ± 0.46 to 9.79 ± 0.39 log CFU/mL. When the pH reached 4.6, there was no difference in population (Table 1), which is in accordance with previous results obtained by Elkhtab et al (2017) and from fermented cow milk using similar cultures (Rubak et al, 2020). However, the fermentation time to reach pH 4.6 was different between isolates that ranged from 18 to 48 h with titratable acidity ranging from 0.77 ± 0.06 to 0.94 ± 0.04%.…”
Section: Characteristics Of Goat Milk Fermented By Lab From Fermented Food and Breast Milksupporting
confidence: 90%
“…Viable counts of the LAB ranged from 9.18 ± 0.46 to 9.79 ± 0.39 log CFU/mL. When the pH reached 4.6, there was no difference in population (Table 1), which is in accordance with previous results obtained by Elkhtab et al (2017) and from fermented cow milk using similar cultures (Rubak et al, 2020). However, the fermentation time to reach pH 4.6 was different between isolates that ranged from 18 to 48 h with titratable acidity ranging from 0.77 ± 0.06 to 0.94 ± 0.04%.…”
Section: Characteristics Of Goat Milk Fermented By Lab From Fermented Food and Breast Milksupporting
confidence: 90%
“…For example, the main group of lactobacilli in the kefir culture has a strong decomposing effect on milk protein in milk (Dallas et al, 2016). Lactic acid bacteria such as Lactobacillus delbrueckii, Lactococcus lactis, Lentilactobacillus kefiri, Streptococcus thermophilus, Lactobacillus acidophilus, Lacticaseibacillus casei, and Lactobacillus helveticus can produce angiotensin converting enzyme (ACE) inhibitory peptides (Fuglsang et al, 2003;Ramchandran and Shah, 2008;Rai et al, 2017;Daliri et al, 2018;Wu et al, 2019;Rubak et al, 2020). In addition, in Lactococcus lactis, starter lactocepin specificity type may have an important influence on the level of bitterness in low salt-in-moisture cheeses (Pillidge et al, 2003).…”
Section: Degradation Of Proteinsmentioning
confidence: 99%
“…One previous study reported that administration with the ACE2 activator or with ANG-(1–7) during pregnancy could alleviate cardiovascular dysfunction in adult SHR offspring [ 92 ]. Another report showed that the antihypertensive effect of probiotics might be due to their ability to produce ACE inhibitory peptides [ 93 ].…”
Section: Implications Of Gut Microbiota In the Developmental Origins Of Cvdmentioning
confidence: 99%